Age Related Histomorphological Changes in Aorta of Pig (Sus scrofa) - Rachel, Sharolin; Ramayya, P. Jagapathi; Santhi, Lakshmi M.; Botlagunta, Supriya; Raja, K.; Chakravarthy, M. Kalyan (International Journal of Bio-resource and Stress Management, 2025)
The present study was conducted during 2022 for a period of ten months ( January to October) in the Department of Veterinary Anatomy, in collaboration with ICAR-AICRP on pigs, C.V.Sc Tirupati, Andhra Pradesh, India on aorta of pigs (Sus scrofa). A total of 18 samples of thoracic and abdominal aorta were collected irrespective of sex of the animal. The samples were divided into three groups based on their age i.e., Group I (up to six months), Group II (seven months to one year) and Group III (above one year) and in each group six animals were studied for recording age-related histomorphological changes. In histomorphological study it was observed that the walls of both thoracic and abdominal aorta were made up of three layers viz., tunica intima, tunica media and tunica adventitia. The tunica intima was made up of endothelium, subendothelial tissue and internal elastic membrane. The thickness of tunica intima increased with advancement of age in both thoracic and abdominal aorta due to increase in the number of musculo-elastic layers. The thickness of tunica media increased with advancement of age of the pigs i.e., from group-I to group-II and decreased in group-III pigs in both thoracic and abdominal aorta. The thickness of tunica adventitia of thoracic aorta was less, when compared to tunica adventitia of abdominal aorta. The separate external elastic membrane was not identified in the aorta since it was merged with the adjacent elastic fibres. In the tunica adventitia numerous small blood vessels and few nerve fibres were observed.